Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Please explain how to solve -the assertion and reason.

Please explain how to solve -the assertion and reason.

Question Image
Grade:11

1 Answers

Aditya Gupta
2080 Points
2 years ago
this ques is extremely easy.
let h(x)= ln(f(x)+f’(x)+...+f(n)(x))
then h(b)-h(a)= ln[(f(b)+f’(b)+...+f(n)(b))/(ln(f(a)+f’(a)+...+f(n)(a))]=b – a (given)
so that [h(b)-h(a)]/[b-a] = 1
however, by rolles theorem [h(b)-h(a)]/[b-a] = h’(c) for some c in (a,b)
or 1= h’(c)
but h(x)= ln(f(x)+f’(x)+...+f(n)(x)) which implies h’(x)= [1/(f(x)+f’(x)+...+f(n)(x))]*[f’(x)+f”(x)+...+f(n+1)(x)]
so h’(c)=  [1/(f(c)+f’(c)+...+f(n)(c))]*[f’(c)+f”(c)+...+f(n+1)(c)] = 1
or f’(c)+f”(c)+...+f(n+1)(c)= f(c)+f’(c)+...+f(n)
or f(n+1)(c)=f(c)
hence statement 2 correctly explains stat 1.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free